Reflexões sobre a opressão do corpo da criança pequena na Educação Infantil - Sudo, Desiree Iasmin Cristiana Pereira (Universidade Federal de São Carlos, 2024)
This Undergraduate thesis discusses addresses the corporal disciplining of young children in the context of Early Childhood Education, with special emphasis on daycare center. The research, which was carried out through a bibliographical review and field study, examines the topic based on the author's personal and professional experience, which found that very young children are often restricted in their freedom of movement at school, whether through norms and punishments, whether through the organization of spaces and times. The study highlights the fundamental importance of playing for the physical, motor, cognitive and emotional development of children, as it allows them to explore themselves, environments, materialities, relationships and, thus, build knowledge, identity and exercise autonomy. Research has found that corporal disciplining can have adverse consequences for child development, including behavioral problems, learning difficulties, low self-esteem and physical and mental health complications. The urgent need for a review in the organization and provision of Early Childhood Education for very young children is emphasized, recognizing the need for children to move. It is proposed to create a welcoming school environment for children, which allows children to express themselves freely, including through body movement.
Reflections on the oppression of the young child's body in Early Childhood Education
Keywords: Educação Infantil; Early Childhood Education; Criança; Child; Corpo; Body; Disciplina; Discipline; Movimento; Movement; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO PRE-ESCOLAR